Propuesta de una guía didáctica metodológica para la enseñanza de la danza kichwa y shuar a los estudiantes de segundo año de básica de la unidad educativa “Juan xxiii” - Once Villegas, José Alberto (2016)
The present research work addressed the central problem, how will the establishment of a methodological didactic guide for the teaching of Kichwa and Shuar dance in the teachers and sophomores in the Basic Unit of the Educational Unit "Juan XXIII ", In Canton Tena, and Napo Province? Within this framework, it was proposed both general and specific objectives that allow classroom teachers or teachers to know the causes that generate the practice of Kichwa Dance and Shuar in students. In order to be able to develop this research, the research methods were determined: the Scientific, Inductive-Deductive, Analytical-Synthetic, Descriptive, technique and instruments were the survey through the questionnaires applied to the teachers and the test that was given Apply to boys and girls. The type of research was not experimental with a qualitative approach. The population and sample was established by 7 teachers and 102 children belonging to the institution. We conclude that based on the analysis carried out, on the teaching of dance Kichwa and Shuar, and through all the methods described in our research carried out by the preparation of teachers acquiring practical theoretical knowledge can be transmitted to children teaching learning Of the Kichwa and Shuar dance. Recommending that with the theoretical knowledge of teachers and the practice of the different movements and basic steps of the Kichwa and Shuar dance of children, self-confidence is generated in their skills and skills to improve their coordination in these Types of ancestral dances.